Chemical weapons as potential tools in terrorist attacks – risks and preventive action - Andrzej Czop (Security and Defence Quarterly, 2019)
This publication looks at shopping malls as a specific category of public facilities. It includes a diagnosis of their safety, pointing to specific irregularities and negligence that threaten them with exposure to possible terrorist attacks. The current international situation is examined, including the crisis that arose as a result of uncontrolled mass migration, which implied an increased threat from Islamic terrorism, which Europe has not yet learned to effectively respond to. A particularly dangerous instrument that can be used by modern terrorists is the chemical weapon. We give examples of its use in acts of terror. The research indicates that a high level of security for public facilities such as large commercial outlets, which accumulate a large number of customers in their premises, is a very important issue. The use of chemical weapons in shopping malls could lead to significant loss of civilian life, as civilians would be a defenceless target. The research process carried out by the author finally drew the conclusion that the current level of security for large-format retail centres does not provide optimal protection in the event of a chemical weapon attack. Therefore, implementing the articles recommendations should positively affect the diagnosed situation and have a significant impact on the improvement of the safety standards in public buildings such as shopping malls.